(untitled) (Journal of Health, Population and Nutrition, 2012)
Women in developing countries experience postnatal depression at rates that are comparable with or higher than those in developed countries. However, their personal experiences during pregnancy and childbirth have received little attention in relation to postnatal depression. In particular, the contribution of obstetric complications to their emotional well-being during the postpartum period is still not clearly understood. This study aimed to (a) describe the pregnancy and childbirth experiences among women in Bangladesh during normal childbirth or obstetric complications and (b) examine the relationship between these experiences and their psychological well-being during the postpartum period. Two groups of womenone group with obstetric complications (n=173) and the other with no obstetric complications (n=373)were selected from a sample of women enrolled in a community-based study in Matlab, Bangladesh. The experiences during pregnancy and childbirth were assessed in terms of a five-point rating scale from severely uncomfortable=1 to not uncomfortable at all=5. The psychological status of the women was assessed using a validated local version of the Edinburgh Postnatal Depression Scale (EPDS) at six weeks postpartum. Categorical data were analyzed using the chi-square test and continuous data by analysis of variance. Women with obstetric complications reported significantly more negative experiences during their recent childbirth [95% confidence interval (CI) 1.36-1.61, p<0.001] compared to those with normal childbirth. There was a significant main effect on emotional well-being due to experiences of pregnancy [F (4,536)=4.96, p=0.001] and experiences of childbirth [F (4,536)=3.29, p=0.01]. The EPDS mean scores for women reporting severe uncomfortable pregnancy and childbirth experiences were significantly higher than those reporting no such problems. After controlling for the background characteristics, postpartum depression was significantly associated with women reporting a negative childbirth experience. Childbirth experiences of women can provide important information on possible cases of postnatal depression. DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11310 J HEALTH POPUL NUTR 2012 Jun;30(2):172-180